2018
DOI: 10.17221/212/2016-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Does dikegulac affect in vitro shoot proliferation and hyperhydricity incidence in olive explants?

Abstract: Dikegulac was tested as a lateral shoot-inducing agent on micropropagated olive (Olea europaea ‘Chondrolia Chalkidikis’) shoots. Rugini olive medium was supplemented with dikegulac at 0, 16.9, 33.8, 66.7, 100.5 or 133.4 μΜ. Dikegulac was not phytotoxic and the explants treated with 100.5 μΜ had higher number, length, and weight of new shoots. Hyperhydricity (or vitrification) symptoms were diminished by increasing dikegulac concentration in the medium dose (66.7–133.4 μΜ). Also, dikegulac stimulated the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…BA (6-benzyladenine) was comparable to zeatin for shoot regeneration from nodal explants of the Olive “Gemlik” [ 1 ]. The use of a combination of BA μΜ dikegulac enhanced shoot proliferation of olive tree cv “Chondrolia Chalkidikis” and the production of new shoots of good quality, diminishing vitrification symptoms [ 20 ]. Additionally, BAP (6-benzylaminopurine) and 2iP (dimethyl-allyl-aminopurine) were tested but, on some cultivars, produced results inferior to zeatin at the end of proliferation [ 21 ] or, as in the case of BAP, provided the best results in combination with zeatin [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…BA (6-benzyladenine) was comparable to zeatin for shoot regeneration from nodal explants of the Olive “Gemlik” [ 1 ]. The use of a combination of BA μΜ dikegulac enhanced shoot proliferation of olive tree cv “Chondrolia Chalkidikis” and the production of new shoots of good quality, diminishing vitrification symptoms [ 20 ]. Additionally, BAP (6-benzylaminopurine) and 2iP (dimethyl-allyl-aminopurine) were tested but, on some cultivars, produced results inferior to zeatin at the end of proliferation [ 21 ] or, as in the case of BAP, provided the best results in combination with zeatin [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperhydricity (vitrification) is one of the problems encountered in micropropagation. Vitrified shoots have smaller internodes and poor rooting ability [ 64 ]. No hyperhydricity was observed during our tests.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is a naturally occurring compound and very economical. Antonopoulou et al, 2018 studied the use of Dikegulac on olive intensive proliferation and found that it is not phytotoxic and much cheaper than zeatin. Sweeta et al, 2019 determined the effect of combination of coconut water, cytokinin and light intensity for enhanced direct in vitro organogenesis of olives (Table 3).…”
Section: Shoot Proliferationmentioning
confidence: 99%